ON THE MASS-RATIO OF THE ECLIPSING BINARIES OF W UMa TYPE - Niarchos, P. G.; Dnerbeck, H. W. (Одеські астрономічні публікації, 2017)
The discrepancy between the photometric and spectroscopic mass-ratio in W UMa-type systems is examined by using all the available mass-ratio data derived by modern techniques from photoelectric and radial velocity curves. The new additional data confirm, with few exceptions, the dependence of the discrepancy on the spectral type, first established by Niarchos and Duerbeck (1991). It is suggested that this discrepancy may be due to the influence of a global circulation pattern on the measured radial velocities.